Benzothiazolium Single Crystals: A New Class of Nonlinear Optical Crystals with Efficient THz Wave Generation. Issue 30 (7th June 2017) - Lee, Seung‐Heon; Lu, Jian; Lee, Seung‐Jun; Han, Jae‐Hyun; Jeong, Chan‐Uk; Lee, Seung‐Chul; Li, Xian; Jazbinšek, Mojca; Yoon, Woojin; Yun, Hoseop; Kang, Bong Joo; Rotermund, Fabian; et al.
Abstract : Highly efficient nonlinear optical organic crystals are very attractive for various photonic applications including terahertz (THz) wave generation. Up to now, only two classes of ionic crystals based on either pyridinium or quinolinium with extremely large macroscopic optical nonlinearity have been developed. This study reports on a new class of organic nonlinear optical crystals introducing electron‐accepting benzothiazolium, which exhibit higher electron‐withdrawing strength than pyridinium and quinolinium in benchmark crystals. The benzothiazolium crystals consisting of new acentric core HMB (2‐(4‐hydroxy‐3‐methoxystyryl)‐3‐methylbenzo[d]thiazol‐3‐ium) exhibit extremely large macroscopic optical nonlinearity with optimal molecular ordering for maximizing the diagonal second‐order nonlinearity. HMB‐based single crystals prepared by simple cleaving method satisfy all required crystal characteristics for intense THz wave generation such as large crystal size with parallel surfaces, moderate thickness and high optical quality with large optical transparency range (580–1620 nm). Optical rectification of 35 fs pulses at the technologically very important wavelength of 800 nm in 0.26 mm thick HMB crystal leads to one order of magnitude higher THz wave generation efficiency with remarkably broader bandwidth compared to standard inorganic 0.5 mm thick ZnTe crystal. Therefore, newly developed HMB crystals introducing benzothiazolium with extremely large macroscopic optical nonlinearity are very promising materials for intense broadband THz wave generation and other nonlinear optical applications. Abstract : A new class of nonlinear optical crystals introducing benzothiazolium exhibit large macroscopic optical nonlinearity with optimal molecular ordering and suitable crystal characteristics for intense terahertz (THz) wave generation. This results in one order of magnitude higher THz wave generation efficiency with considerably broader bandwidth than inorganic standard ZnTe crystal when pumped at the technologically important wavelength of 800 nm.